Randomized Trial of Olaparib With or Without Cediranib for Metastatic Castration-Resistant Prostate Cancer: The Results From National Cancer Institute 9984. Issue 4 (1st February 2023) - Kim, Joseph W.; McKay, Rana R.; Radke, Marc R.; Zhao, Shilin; Taplin, Mary-Ellen; Davis, Nancy B.; Monk, Paul; Appleman, Leonard J.; Lara, Primo N.; Vaishampayan, Ulka N.; Zhang, Jingsong; Paul, Asit K.; et al.
Abstract : PURPOSE: Cediranib, a pan-vascular endothelial growth factor receptor inhibitor, suppresses expression of homologous recombination repair (HRR) genes and increases sensitivity to poly-(ADP-ribose) polymerase inhibition in preclinical models. We investigated whether cediranib combined with olaparib improves the clinical outcomes of patients with prostate cancer. METHODS: Patients with progressive metastatic castration-resistant prostate cancer (mCRPC) were randomly assigned 1:1 to arm A: cediranib 30 mg once daily plus olaparib 200 mg twice daily or arm B: olaparib 300 mg twice daily alone. The primary end point was radiographic progression-free survival (rPFS) in the intention-to-treat patients. The secondary end points were rPFS in patients with HRR-deficient and HRR-proficient mCRPC. RESULTS: In the intention-to-treat set of 90 patients, median rPFS was 8.5 (95% CI, 5.4 to 12.0) and 4.0 (95% CI, 3.2 to 8.5) months in arms A and B, respectively. Cediranib/olaparib significantly improved rPFS versus olaparib alone (hazard ratio [HR], 0.617; 95% CI, 0.392 to 0.969; P = .0359). Descriptive analyses showed a median rPFS of 10.6 (95% CI, 5.9 to not assessed [NA]) and 3.8 (95% CI, 2.33 to NA) months (HR, 0.64; 95% CI, 0.272 to 1.504) among patients with HRR-deficient mCRPC, and 13.8 (95% CI, 3.3 to NA) and 11.3 (95% CI, 3.8 to NA) months (HR, 0.98; 95% CI, 0.321 to 2.988) among patients with BRCA2 -mutated mCRPC in arms A and B, respectively. The incidence of grades 3-4 adverse events was 61% and 18% in arms A and B, respectively. CONCLUSION: Cediranib combined with olaparib improved rPFS compared with olaparib alone in men with mCRPC. This combination was associated with an increased incidence of grades 3-4 adverse events. BRCA2 -mutated subgroups treated with olaparib with or without cediranib were associated with a numerically longer median rPFS.